A Comparative Study of Futsal Training Techniques on Concentration and Gross Motor Skills in New and Long-Term Students at MR Futsal Academy (Aged 4–7 Years) - Febrianti, Talin Salma; Ekanesia, Pratidina (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to compare the effects of futsal training techniques on concentration and gross motor skills among early childhood students at MR Futsal Academy (ages 4–7). Using a quantitative comparative method, data were collected through observation and interviews with coaches and academy management. The research compared the abilities of new students and long-term students in terms of basic futsal techniques, concentration, and gross motor skills. The results showed that long-term students had significantly better gross motor abilities than new students, indicating a strong contribution of structured futsal training to physical coordination. However, no statistically significant difference was found in concentration, although descriptive data showed a positive trend. The correlation between futsal skills and both concentration and motor skills was positive but not statistically strong. These findings suggest that gross motor development benefits directly from physical training, while cognitive and psychological factors beyond the training environment may influence concentration.